Heliaquanoids A–E, five sesquiterpenoid dimers from Inula helianthus-aquatica - Zheng, Zai-Qin; Wei, Wen-Jun; Zhang, Junmin; Li, Hang-Ying; Xu, Kai; Xu, Jiayuan; Tang, Bencan; Li, Ya; Gao, Kun (American Chemical Society, 2019)
Heliaquanoid A (1), the first exo-2,4-linked Diels−Alder adduct between a pseudoguaianolide dienophile and a guaianolide diene, and heliaquanoids B−E (2−5), four new 2,4-linked Diels−Alder adducts between a xanthanolide dienophile and a guaianolide diene, were isolated from stems and leaves of Inula helianthus-aquatica. Their structures were determined by the NMR spectroscopy, modified Mosher′s method, electronic circular dichroism, and X-ray diffraction analysis. Compounds 2 and 3 exhibited moderate cytotoxic activities against HL-60 cells with IC50 values of 7.5 and 4.9 μM, respectively.